Student Perspective: Margaret Chase Smith Library 2012 Essay Contest - Sargent, Derek (Maine Policy Review, 2012)
Each year, the Margaret Chase Smith Library sponsors an essay contest for high school seniors. This year, students were invited to assess the current state of national affairs and describe their vision of the American Dream for the 21st century. We feature here the 2012 first-place prize-winning essay.